Effect of flexible family visitation on delirium among patients in the Intensive Care Unit: the ICU visits randomized clinical trial - Rosa, Regis Goulart (2019)
Fernando Augusto Bozza. Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta a informação no documento.